Doxorubicin-polyglycerol-nanodiamond composites stimulate glioblastoma cell immunogenicity through activation of autophagy. (1st March 2019) - Li, Tong-Fei; Xu, Yong-Hong; Li, Ke; Wang, Chao; Liu, Xin; Yue, Yuan; Chen, Zhuo; Yuan, Shen-Jun; Wen, Yu; Zhang, Quan; Han, Min; Komatsu, Naoki; et al.
Graphical abstract: Abstract: Immunosuppression is a salient feature of GBM associated with the disease's grim prognosis and the limited success of anti-GBM immunotherapy. Stimulating immunogenicity of the GBM cells (GC) is a promising approach to subverting the GBM-associated immunosuppression. We had previously devised a drug composite based on polyglycerol-functionalized nanodiamonds bearing doxorubicin (Nano-DOX) and demonstrated that Nano-DOX effectively modulated GBM's immunosuppressive microenvironment through stimulating the immunogenicity of GC and initiated anti-GBM immune responses. The present study now explored the mechanism of Nano-DOX's immunostimulatory action. Nano-DOX was found to induce autophagy rather than apoptosis in GC and stimulated GC to emit antigens and damage-associated molecular patterns (DAMPs) that are potent adjuvants, which resulted in enhanced activation of dendritic cells (DC). Heightened autophagosome release was observed in Nano-DOX-treated GC but was shown not to be a major channel of antigen donation. Blocking autophagy in GC not only reduced Nano-DOX-stimulated GC antigen donation and DAMPs emission, but also efficiently attenuated DC activation stimulated by Nano-DOX-treated GC. Taken together, these findings suggest that activation of autophagy is a central mechanism whereby Nano-DOX stimulates GC's immunogenicity. Our work provides new insight on how nanotechnology can be applied to therapeutically modulate the GBM immune microenvironment by harnessing autophagy in the cancer cells. Statement of Significance: Immunosuppression is a salient feature of GBM associated with the grim prognosis of the disease and the limited success of anti-GBM immunotherapy. We demonstrated that Doxorubicin-polyglycerol-nanodiamond composites could activate autophagy in GBM cells and thereby stimulate the immunogenecity of GBM cells. This discovery 1, sheds new light on how nanotechnology could be applied to therapeutically modulate the tumor immune microenvironment, and 2, provides a powerful tool for subverting the GBM's immunosuppressive microenvironment, which has great therapeutic potential for the treatment of GBM.